Estimation of winding insulation resistance to the corona discharges; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Leonov A. P. Andrey Petrovich (2014, 2014)
Title screen